2021
DOI: 10.1021/acsanm.1c00391
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Curie Temperature and Magnetic Anisotropy in Nanoscale-Layered Cr2Te3 Films: Implications for Room-Temperature Spintronics

Abstract: Nanoscale-layered ferromagnets have demonstrated fascinating two-dimensional magnetism down to atomic layers, providing a peculiar playground of spin orders for investigating fundamental physics and spintronic applications. However, the strategy for growing films with designed magnetic properties is not well established yet. Herein, we present a versatile method to control the Curie temperature (T C ) and magnetic anisotropy during the growth of ultrathin Cr 2 Te 3 films. We demonstrate an increase of the T C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 65 publications
4
20
0
Order By: Relevance
“…24 Figure S3a shows the X-ray diffraction (XRD) pattern of Cr 2 Te 3 nanosheets, again confirming the single crystalline and hexagonal crystal structure (PDF 29-0458). 30 Additionally, Raman spectrum of Cr 2 Te 3 nanosheet (Figure S3b) shows two characteristic peaks at 122.1 and 139.3 cm −1 , which is consistent with the previously reported results. 31 To investigate the magnetic properties of the CVD-synthesized Cr 2 Te 3 nanosheets, we measured the magnetization using VSM from a physical property measurement system (PPMS).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…24 Figure S3a shows the X-ray diffraction (XRD) pattern of Cr 2 Te 3 nanosheets, again confirming the single crystalline and hexagonal crystal structure (PDF 29-0458). 30 Additionally, Raman spectrum of Cr 2 Te 3 nanosheet (Figure S3b) shows two characteristic peaks at 122.1 and 139.3 cm −1 , which is consistent with the previously reported results. 31 To investigate the magnetic properties of the CVD-synthesized Cr 2 Te 3 nanosheets, we measured the magnetization using VSM from a physical property measurement system (PPMS).…”
supporting
confidence: 92%
“…The corresponding selected area electron diffraction (SAED) pattern in Figure d shows only one set of diffraction spots, which indicates that the CVD-synthesized Cr 2 Te 3 nanosheet is a single crystal material with hexagonal crystal structure (Figure e) Figure S3a shows the X-ray diffraction (XRD) pattern of Cr 2 Te 3 nanosheets, again confirming the single crystalline and hexagonal crystal structure (PDF 29-0458) . Additionally, Raman spectrum of Cr 2 Te 3 nanosheet (Figure S3b) shows two characteristic peaks at 122.1 and 139.3 cm –1 , which is consistent with the previously reported results .…”
mentioning
confidence: 76%
“…The Cr n X (X = S, Se, and Te; 0 ≤ n ≤ 1) family is a non-vdW 2D magnetic material. In recent years, Cr n X has attracted an enormous amount of attention. For the Cr 2 S 3 synthesized by CVD, the temperature can be changed to realize the transition of R 3̅ Cr 2 S 3 from a soft magnetic state to a hard magnetic state, and Cr 2 S 3 was found to have varied electrical properties at different thicknesses . He’s group used CVD to synthesize high-quality ultrathin non-van der Waals single crystal CrSe on a mica substrate, whose horizontal size can reach 150 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Cr 2 X 3 behaves as ferrimagnetic, antiferromagnetic, or fully compensated ferrimagnetic (FCFiM) and ferromagnetic, with X varying from S, Se, and Te, respectively. Cr 2 S 3 and Cr 2 Se 3 have been studied for their low thermal conductivity as thermoelectric materials. , However, experimental studies on Cr 2 S 3 showed its ferrimagnetic and narrow gap semiconducting property with its thickness-dependent carrier-type (electrons and holes) transition. , Cr 2 Se 3 exhibits AFM and metallic property. , However, there has been a report of semiconducting Cr 2 Se 3 and ferri-like behaviors because of the noncollinear spin behavior of the magnetic structure. , Cr 2 Te 3 is metallic with FM order. Recent studies have shown noncollinear spin order, ultrahigh coercivity, and tunable critical temperature. , Although there have been some efforts made in the computational study of these materials, ,,, a systematic approach for this unique covalently layered structure of Cr 2 X 3 is still lacking.…”
Section: Introductionmentioning
confidence: 99%